High lonesome - Le May, Alan, 1899-1964; Barrymore, John, 1932-2004; Le May-Templeton Pictures; Cinetel Films ([Los Angeles, CA] : Le May-Templeton Pictures, 1950)
When a sudden spurt of murders occurs in the Big Bend country, suspicion immediately falls on a young drifter who just moved to the area. --
John Drew Barrymore, Chill Wills, John Archer, Lois Butler, Jack Elam
Cinematographer, W. Howard Greene; editor, Toby Shimin; music, Rudy Schrager.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 26, 2016)
Keywords: Western films; Internet videos; Streaming video